PENGARUH LITERASI TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP KEAKTIFAN BELAJAR DAN HASIL BELAJAR EKONOMI SISWA - Ilham, Muhammad; Elpisah, Elpisah; Nurdin, Nurdin (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This study aims to determine (1) the process of implementing information technology literacy in class XI of SMAN 4 Pangkep, (2) the effect of information and communication technology (ICT) literacy on student learning activeness, and (3) the effect of ICT literacy on student learning outcomes. The method used is quantitative with a causal associative approach. The research instruments were questionnaires and post-test questions. The study population consisted of 70 students of class XI IPS SMAN 4 Pangkep, with sampling techniques from the population. Data analysis was conducted using simple linear regression. The results showed that (1) students' ICT literacy skills were in the high category with a percentage of 69%, (2) student learning activeness was in the high category with a percentage of 58%, and (3) student learning outcomes were in the high category with a percentage of 40%. In addition, ICT literacy has a significant influence on student learning activeness and learning outcomes, with the value of Thitung (5.201) and (8.828) more significant than Ttabel (1.661), as well as significance (0.001) and (0.002) smaller than 0.05. Thus, it can be concluded that digital literacy positively and significantly affects student activeness and learning outcomes.